The concept of health and the difference between prevention and promotion - Dina Czeresnia
In this article the author presents a point of view which she considers central to understanding the difference between prevention - associated with the traditional discourse of public health - and health promotion, an idea in connection with which proposals are now being presented for rethinking and redirecting public health practices. This perspective relates to the limits of the health and disease concepts in relation to the concrete experiences of health and illness. On the one hand, practical awareness of this limit implies far-reaching changes in the way scientific knowledge is related to (and used in) the formulation and organization of health practices; on the other, health promotion projects also avail themselves of the concepts guiding the discourse of prevention. This leads to certain difficulties that appear as inconsistencies or gray areas in the operationalization of promotion projects, which do not always succeed in asserting their nature as distinct from traditional preventive practices.